Policies for a climate-neutral industry Lessons from the Netherlands - Anderson, Brilé (OECD Publishing, 2021)
This paper presents a comprehensive assessment of the policy instruments adopted by the Netherlands to reach carbon neutrality in its manufacturing sector by 2050. The analysis illustrates the strength of combining a strong commitment to raising carbon prices with ambitious technology support, uncovers the pervasiveness of competitiveness provisions, and highlights the trade-off between short-term emissions cuts and longer-term technology shift. The Netherlands' carbon levy sets an ambitious price trajectory to 2030, but is tempered by extensive preferential treatment to energy-intensive users, yielding a highly unequal carbon price across firms and sectors. The country's technology support focuses on the cost-effective deployment of low-carbon options, which ensures least-cost decarbonisation in the short run but favours relatively mature technologies. The paper offers recommendations for policy adjustments to reach the country's carbon neutrality objective, including the gradual removal of exemptions, enhanced support for emerging technologies and greater visibility over future infrastructure plans
Keywords: Science and Technology; Netherlands